Quasi-spatial method for finding optimal design angles for the entrance and exit of blade crowns of the axial compressor of a gas turbine engine - Терещенко, Ю. М.; Дихановський, В. М.; Волянська, Л. Г.; Юрченко, О. В. (Proceedings of National Aviation University (archive), 2020)
The main provisions of the quasi-spatial optimization method are describedconstructive angles of entry and exit of blade crowns of the axial compressor, whichtakes into account the difference between the shape of the worktops in the state of rest and at workin the calculation mode and redistribution of losses of kinetic energy at the height of the shoulder blade. Calculated parameters of the gas flow in the flow part of the degree carried outthe solution of the complete system of Navier-Stokes equations